2015
DOI: 10.1080/17415977.2015.1055262
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in stable inversion of NARX models by using Mann iteration

Abstract: The use of Mann iteration in the stable inversion of NARX models that have been converted to state space form is investigated to either recover the convergence or improve the accuracy of the best approximate solution under conditions when Picard iteration fails to converge. Attention is given to the use of filtering and time-varying iteration gains. The results are potentially of use in response reconstruction for fatigue testing purposes where the inverse of a NARX model, obtained by system identification, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 13 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…These results do not represent an improvement on the results of stable inversion Eq. 79 for the same desired input and output signal in Example 3 of [13], for which we get lower input and output errors of 13.3% and 8.1% respectively. It is found that in all cases except when using no Q filter the best ILC results were obtained using iteration-dependent ILC gains.…”
Section: Example 3: Ilc Using An Approximate Linear Inverse Modelmentioning
confidence: 76%
See 3 more Smart Citations
“…These results do not represent an improvement on the results of stable inversion Eq. 79 for the same desired input and output signal in Example 3 of [13], for which we get lower input and output errors of 13.3% and 8.1% respectively. It is found that in all cases except when using no Q filter the best ILC results were obtained using iteration-dependent ILC gains.…”
Section: Example 3: Ilc Using An Approximate Linear Inverse Modelmentioning
confidence: 76%
“…Finally, we also note that the use of Mann [12] and Ishikawa iteration in stable inversion [13] has an analogy in ILC in that the conventional and alternative ILC algorithms developed here both have parallels in the Picard and Mann iteration schemes. It is furthermore shown that the application of Ishikawa iteration to ILC result in novel ILC iteration schemes for both the conventional and alternative ILC algorithms.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…which enables the synthesis of the ILILC learning matrix (31). With this, the complete synthesis of ILILC with stable inversionstarting from a model in the normal form ( 12)-can be summarized by Procedure 1.…”
Section: Initial Picard Iteratẽ (0) Selection and Implementationmentioning
confidence: 99%